Attacker standard for secure routing protocols - Divya, Ms; R. Gobinath, Dr (International Journal of Engineering and Technology, 2018)
The secured routing protocol expresses an underlying elementary unit confide in information interchanging system. Miserably, presently no anatomy remains to supports in the layout and inquiry of secured routing protocols. This work investigates the structured approaches of secured routing and the interrelating attacker standards to contribute a structure for modeling prime protocols. Based on this anatomy, it is detected that the powerful attacks are targeting the data in the control plane. In this paper the strength of attackers are classified with respect to the locations under its direct control.Â Â